Einfluss der Betriebstemperatur auf den Wirkungsgrad von Modul-Wechselrichtern für PV-Netzeinspeisungen - Krauter, Stefan; Bendfeld, Jörg (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Triggering Demand‒Side‒Management: Correlation of electricity prices, share of renewables, CO2‒contents, and grid‒frequency in the German electricity grid. - Krauter, Stefan; Zhang, L. (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020.)
To provide a simple instrument to operate residential Load-Shifting or Demand-Side-Management systems, the measurement of the actual grid frequency seems to be an appropriate method. Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation. While the specific CO2- emission is decreasing then ‒ due to the increased share of Renewables, the grid frequency is increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side management indicator to lower specific CO2‒emssions and costs (if a dynamic consumption tariff is available). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and a the correlation between grid frequency, power surplus, share of renewables vs. CO2-contents and price at the European energy exchange (EEX) have been calculated. The results show: Correlation between frequency and share of renewables is quite low (r = 0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. There is a good anti-correlation (r = - 0.687) between the EEX‒prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r =0.665), within the one year (2018) that correlation almost doesn’t exist, possibly due to the inflexibility of the bulky lignite power plants that even operate at negative prices.
Keywords: Keywords: Load-Shifting; Demand-Side-Management; DSM; grid frequency; EEX; electricity trading prices; renewable share; flexibility; emissions; CO2

Reduction of required storage capacities for a 100% renewable energy supply in Germany, if new PV systems are installed with east-west tracking systems at increased elevation angles - Krauter, Stefan; Rustemovic, D.; Khatibi, Arash (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020)
Due to the strong reduction of PV prices, storage plays a dominating role in overall system costs. A steeper elevation angle would result in a more balanced seasonal PV yield, at the cost of PV yield reductions during summer, but allowing reduced storage capacities. Additionally, the effect of a single-axis tracking system has been investigated, generating more electricity during the morning and evening hours, thus reducing daily storage requirements. The necessary PV size and storage capacities required for the German energy supply (1,500 TWh after electrification of all sectors) via 100% renewable energies and a 50% solar share have been calculated via the HOMER Pro software, considering the bridging of periods of "dark lulls“ in winter, using costs of 2030 (Table 1). Results: The increase of module elevation angles above the typical 30° leads to a reduction of investment and supply costs. The optimum is reached at a cost reduction of -1.5% for an elevation angle at the latitude of the installation site. An explanation is that high elevation angles are favorable for clear winter days, but not at all for the critical days with diffuse irradiance only, so the battery capacity must be increased. For the same reason, tracking systems do not offer any cost advantage (at least for the ones without an option for horizontal positioning during diffuse days).
Keywords: Energy Storage; PV system integration; Large Grid-connected PV systems; Simulation; Energy Supply Options

Elevated Temperatures Affecting Efficiency, Overall Performance and Energy Yield of PV Microinverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EU PVSEC 2020)
During comparative measurements of different PV microinverters, two yield issues came up that could not be explored via conventional efficiency measurements, but do have a significant impact on electrical energy yield: First category of issues are either sluggish or nervously acting maximum–power–point–tracking devices, which lead to reduced energy yields. The other category of issues is thermal: As a first explanation for observed reduced energy yields, it has been assumed that the conversion efficiency degrades at higher operating temperatures. This matter has been investigated in this article: A change in conversion efficiency could not be observed for elevated operation temperatures up to 50°C, despite high-precision and repeated measurements. But it was found that some inverters temporarily interrupted (or entirely stopped) operation after long periods of running at high temperatures. Also, a reduction in potential maximum power output has been detected for those inverters. Summarizing: With a high degree of certainty it can be stated that those reported yield losses have been caused by the temporary shutdowns and power limitations of the inverters.
Keywords: AC-modules; Microinverter; Power Conditioning; Thermal Performance; Ventilation; Stability; Efficiency; Yield

Correlation of grid-frequency, electricity prices, share of Renewables and CO2-contents of German electricity grid to enable inexpensive triggering of Demand-Side-Management - Krauter, Stefan; Zhang, L. (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) 2020)
Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation in the German electricity grid. While the specific CO2-emission is decreasing then - due to the increased share of Renewables, the grid frequency should be increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and -off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side-management indicator to lower specific CO2-emissions and costs (if a dynamic consumption tariff is applied). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and the correlations between grid frequency, share of renewables, CO2-contents, and actual price at the European energy exchange (EEX) have been calculated. The results show: Correlation between grid frequency and the share of renewables is quite low (r=0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. As expected, there is a good anti-correlation (r=-0.687) between the EEX-prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r=0.665), within the one year (2018) that correlation almost doesn't exist, possibly due to the inflexibility of the bulky lignite baseload power plants that even operate at negative prices.
Keywords: CO2; EEX; Grid frequency; DSM; electricity price; Renewable share

Comparison of Microinverters: Update on Rankings of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) JUNE 15 - AUGUST 21, 2020 VIRTUAL MEETING)
To compare efficiency and yield of many micro-inverters available on the world market in 2014-2020, an in- and outdoor test laboratory at the University of Paderborn has been set up. The inverters have been fed by identical and calibrated crystalline silicon PV modules of 215 Wp. To monitor accurately DC input, AC power output and energy yield, each of the micro-inverters has been equipped with a calibrated electricity meter. For micro-inverters requiring control units for grid-feeding that has been acquired also. The comparison covers efficiency-load characteristics as well as electrical energy yields. Purchase costs vary considerably between the models in comparison, sometimes inverter costs are higher than module costs, particularly if an additional grid-connection or interface device is needed for operation. The weighted conversion efficiency according to EU and CEC standards has been measured and calculated. While some inverters have been optimized for high irradiance levels, they ranked better at the CEC efficiency, others performed very well also for low irradiance levels, thus ranking higher at in the EU-efficiency tables. These results are deviating from the actual energy yield measurements, which show a slightly different ranking. At one inverter, an accurate, but very slow MPPT algorithm that barely could follow quickly changing irradiance levels could be the reason for this effect. Another inverter switched off after operation at high power output for a while. Apparently, some inverters are been optimized to show excellent EU and CEC efficiency ratings. Two of the inverters featuring two inputs did not show an exceptional performance at the EU- and CEC-ratings, but they achieved top ranks at the AC energy yield for the first years. For the customer, the AC yield is a major performance indicator of any microinverter and should be included in the datasheet.
Keywords: yield; AC; micro-inverter; MPPT; CEC rating; EU efficiency; Photovoltaic; Solar

Eignung der Netzfrequenz als Instrument der Entscheidungsfindung zur Auslösung von Lastverschiebungen bei niedrigen spezifischen CO2-Emissionen und EEX-Handelspreisen - Krauter, Stefan; Zhang, L. (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Probability of Correct Decision–Making at Triggering of Load-Shifting Intended for low CO2-intensity and low EEX trading-prices via simple Grid Frequency Monitoring - Krauter, Stefan; Zhang, L. (Proceedings of the 14th International Renewable Energy Storage Conference, Düsseldorf (Deutschland), 10.–12. März 2020 (verschoben: 16.–18. März 2021))

European Investment in Greece in the Nineteenth Century - Schönhärl, Korinna

Die Einstellung angehender Lehrkräfte zu Forschendem Lernen im Praxissemester und Referendariat - Homt, Martina; Bloh, Bea; Grosser, Christine (Forschendes Lernen in der Lehrer/innenbildung. Implikationen für Wissenschaft und Praxis)